Mompreneurs, Leaning In, and Opting Out: Work/Family Choices under Neoliberalism - Wilton, Shauna (Atlantis, 2017)
This article explores three trends in the search for work-life balance and relates these trends to the neoliberal family policy context in Canada. I argue that these models reflect current ideologies about motherhood, the state, and work. Ultimately, they reflect current ideas about intensive mothering and the ‘good mother’ and neoliberal norms surrounding the good worker and citizen.